Busur Creative Community Assistance In Making Educational Media Regarding The Use of Masks in Islamic Boarding Schools (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Data from the World Health Organization (WHO) (2021) reports that Indonesia is ranked 18th in Asia with COVID-19 cases. The number of COVID-19 cases as of May 5, 2021 in Indonesia is 1,686,373 confirmed cases, 1,541,149 patients recovered, and 46,137 people died. Most of the transmission of COVID-19 occurs due to negligence in the use of PPE. Baiturrahman Islamic Boarding School is located in Bojong Rancakole Village, Ciparay District, Bandung Regency, but when conducting an observation survey on February 5 in the Baiturrahman Islamic Boarding School environment there are still many who do not comply with wearing masks. The use of masks is part of a comprehensive series of prevention and control measures that can limit the spread of certain viral respiratory diseases, including COVID-19. Masks can be used either to protect a healthy person (worn to protect themselves when in contact with an infected person) or to control the source (worn by an infected person to prevent further transmission). Busur Creative Community is a community in the Baiturrahman Islamic boarding school engaged in acting and has been present at the Baiturrahman Islamic Boarding School since 2001. This community has made this role-playing specialization one of the "Islamic Da'wah Programs" in Baiturrahman Islamic Boarding School. This specialization was formed as a form to express the Islamic artistic spirit of the students and as a form of Islamic da'wah through the Performing Arts. The Busur Creative Community has a drawback, namely that it has not presented health education yet. With this, we want to assist the Busur Creative Community in making educational media regarding the use of masks in Islamic boarding schools. There was an increase in knowledge for the Busur Creative Community after providing assistance related to making educational videos, and there was an increase in knowledge and attitudes towards awareness of using masks for students of the Biaturrahman Islamic Boarding School after watching videos made by the Busur Creative Community .Keywords :